Produção de materiais adsorventes para remoção de nitrato em meio aquoso - Araujo, Sara Sales de (2019)
Nitrate contamination of surface and groundwater resources has been evident over the years, as high concentrations can cause adverse health reactions such as methemoglobinemia in newborns. In the study carried out in different Brazilian states, nitrate concentration levels above the maximum allowed for potability standards were determined, highlighted as 10mg. L-1 in the consolidation nº 5 of the Ministry of Health. In this context, there was an intensification of studies on the adsorption process using activated bichars and biosorbents, produced from agroindustrial residues to remove nitrate in aqueous medium. The use of corn cob as a precursor is favorable since the imminent generation of these residues. In this study, corncob was chemically modified with P.A. hydrochloric acid to obtain biosorbent (BS), activated biochar of oxidizing atmosphere (BCO) and activated biochar of inert atmosphere (BCI). For the prepared adsorbent materials their characteristics were determined, such as the zero charge point (pHpzc) assay which revealed for BS and BCO pHpzc 2.1, while the BCI was 6.3. In the Forrier Transform Infrared (FTIR) assay the adsorbent materials showed characteristic groups, such as carboxylic (3400 cm-1), methyl, methylene and methoxyls (2900cm-1), carbonyls (1700cm-1), aromatic rings (1600cm-1). Also, the adsorption conditions were optimized regarding the solution pH and adsorbent dosage, revealing solution pH of 2.0 for BS and BCO, and pH of 6 for BCI, and 0,75 g for BS and BCO, 1g for BCI. Adsorption isotherms and kinetics were determined, and Langmuir isotherm was better adapted for BS and Freundlich for BCO and BCI. The kinetics were pseudofirst order for BS and pseudo-second order for BCI and BCO. For the materials presented, removals were 6.16 mg.g -1 for BS, 13.33 mg.g -1 for BCO and 15.54 mg.g -1 for BCI.